Repression of Smad4 by MicroRNA-1285 moderates TGF-β-induced epithelial-mesenchymal transition in proliferative vitreoretinopathy. - Shu-I Pao (Public Library of Science (PLoS), 2021)
The purpose of this study was to assess whether microRNA (miR)-1285 can suppress the epithelial-mesenchymal transition (EMT) in retinal pigment epithelial cells. Expression of miR-1285 was evaluated using quantitative real-time polymerase chain reaction (RT-qPCR). The features of EMT were assessed using Western blotting, immunocytochemical staining, scratch wound healing tests, modified Boyden chamber assay, and collagen gel contraction assay. A rabbit model of proliferative vitreoretinopathy (PVR) was used for in vivo testing, which involved the induction of PVR by injection of transfected ARPE cells into the vitreous chamber. Luciferase reporter assay was performed to identify the putative target of miR-1285. The expression of miR-1285 was downregulated in ARPE-19 cells treated with transforming growth factor (TGF)-β. Overexpression of miR-1285 led to upregulation of zonula occludens-1, downregulation of α-smooth muscle actin and vimentin, cell migration and cell contractility-all EMT features-in the TGF-β2-treated ARPE-19 cells. The reporter assay indicated that the 3' untranslated region of Smad4 was the direct target of miR1285. PVR progression was alleviated in the miR-1285 transfected rabbits. In conclusion, overexpression of miR-1285 attenuates TGF-β2-induced EMT in a rabbit model of PVR, and the effect of miR-1285 in PVR is dependent on Smad4. Further research is warranted to develop a feasible therapeutic approach for the prevention and treatment of PVR.